Pengaruh Harga Pokok Penjualan Terhadap Laba Setelah Pajak - Herman (Jurnal Ekonomi & Bisnis, 2022)
This study aims to determine the effect of cost of goods sold for profit before tax at PT Astra Agro Lestari Tbk. The company is a manufacturing company engaged in processing palm fruit into oil or ingredients for making oil, including cooking oil. The researcher took samples of the cost of goods sold and the company's profit before tax for thirteen years (period), starting from 2009 to 2021. The study used parametric quantitative methods, the type of data used was ratio data, then the hypothesis was associative. The variables used are one independent variable and one dependent variable, so that the measuring instrument used to determine the effect of the independent variable on the dependent variable is simple linear regression analysis. The results of the study is no effect between cost of goods sold and profit before tax at PT Astra Agro Lestari Tbk.